2020
DOI: 10.3390/ijerph17165839
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between School Characteristics and Classroom Radon Concentrations in Utah’s Public Schools: A Project Completed by University Environmental Health Students

Abstract: Radon (²²²Rn), a radioactive gas, is the second leading cause of lung cancer deaths in the U.S. Classroom radon concentrations in public schools in our target area had never been measured or had not been measured in many years. We had university students, primarily enrolled in environmental health courses, measure radon concentrations in 2289 classrooms in 66 of Utah’s public schools and identify school characteristics associated with classroom radon concentrations. The geometric mean (GM) classroom radon conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“… 16 Davis et al found that classroom radon concentrations decreased when school ventilation systems were on. 17 Branco et al reported that radon concentrations in daycare centers and elementary schools in Portugal were related to the year of construction of the buildings. 18 …”
Section: Impacts Of Radon Exposure On Human Healthmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 Davis et al found that classroom radon concentrations decreased when school ventilation systems were on. 17 Branco et al reported that radon concentrations in daycare centers and elementary schools in Portugal were related to the year of construction of the buildings. 18 …”
Section: Impacts Of Radon Exposure On Human Healthmentioning
confidence: 99%
“…(16) Davis et al constataram que as concentrações de radônio nas salas de aula diminuíram quando os sistemas de ventilação das escolas estavam ligados. (17) Branco et al relataram que as concentrações de radônio em creches e escolas primárias de Portugal estavam relacionadas com o ano de construção dos edifícios. (18) Vários fatores foram identificados como capazes de interferir nas concentrações de radônio em ambientes internos: número de ocupantes, ventilação, localização dos ambientes no edifício (19) e fatores relacionados à construção, pois construções localizadas no mesmo substrato geológico, mas com diferentes tipos de materiais de construção podem apresentar diferentes concentrações internas de radônio.…”
Section: Impactos Da Exposição Ao Radônio Na Saúde Humanaunclassified
“…It can penetrate inside buildings through cracks and joints in the foundation and accumulate to high values if the ventilation is poor (Ambrosino et al, 2020). The accumulation of Rn-222 depends on various factors such as geological setting, meteorological condition, buildings characteristic (Levesque et al 1997;Schubert et al, 2018), the type, use, and upkeep of the heating, ventilation, and air conditioning system in the school (Davis et al, 2020) and the inhabitant habits. Radon represents public health problem due to increasing the risk of lung cancer in the population (WHO, 2009).…”
Section: Introductionmentioning
confidence: 99%